Histórias marcadas na pele - Barros, Clarissa Maria Dubeux Lopes (2006)
This research project, referred into psycho-analytical theory, departs from the questioning of what takes a youth to intentionally mark his/her skin with tattoos and similar signs. On the side of the culture inscription with its productions of belonging, the research project will formulate a theorical and investigative systematization about the psychic reality of the youths that have themselves tattooed. The body conception will be contemplated in the study, in meanings through the differents cientific views and its meanings. However it is the psychic representation that will be the problematic in the field of the psycho-analytical theory. Its proper to question the conception of the subject and the language, taking into consideration the language´s dimension steped on the body through phrases and symbols exposed to the other´s eyes. The mark on the skin will be also emphasized in relation to the exclusivity of the maternal love through frequent cases of youths that have themselves tattooed with sentences written in their skin invoking that real love just the mother´s. It´s proper to question about the quality of this relation, trying to confront the factual and mythical character in the subject´s relation with his/her mother. From 7 youths, between 16 and 18 years old, will be listened through the depositions collected form free. These youths are of underpriviledged back-ground and belonged to institutions that develop program of social inclusion, as will as those designated by the state to the minors integral protection in accordance with the brazilian children and adolescent statue. The psychic mechanisms related to the act of making a mark on the body reveals an important way to the comprehension of the subject in the face of questions that cannot be separated of human existence. Being in a social risk situation and make marks on his/her skin, cames up a frontier, an edge, that makes the speeches that testifies the condition to existence of and that appeals for protection circulate